Validation of the Korean version of the Roland–Morris Disability Questionnaire - Lee, Jung Sub (Springer-Verlag, 2011)
We evaluated the reliability and validity of an adapted Korean version of the Roland–Morris Disability Questionnaire (RMDQ). Translation/retranslation of the English version of RMDQ was conducted, and all steps of the cross-cultural adaptation process were performed. The Korean version of the Visual Analog Scale (VAS) measure of pain, RMDQ, and the previously validated Oswestry Disability Index (ODI) were mailed to 100 consecutive patients with chronic lower back pain (LBP) of at least 3 months. Eighty-one patients responded to the first mailing of questionnaires and 63 of the first-time responder returned their second survey. The average age of the 63 patients (45 female, 18 male) was 47.8 years. Reliability assessment was determined by estimating kappa statistics of agreement for each item, the intraclass correlation coefficient (ICC), and Cronbach’s α. Concurrent validity was evaluated by comparing the responses of RMDQ with the results of VAS and responses of ODI by using Pearson’s correlation coefficient. The constructed Bland–Altman plot showed a good reliability. All items had a kappa statistics of agreement greater than 0.6. The RMDQ showed excellent test/re-test reliability as evidenced by the high ICC for 2 test occasions (ICC = 0.932, P < 0.001). Internal consistency was found to be very good at both assessments with Cronbach’s α (0.942 and 0.951 at first and second assessments, respectively). The RMDQ was correlated with the VAS (r = 0.692; P = 0.000 and r = 0.668; P = 0.000 at first and second assessments, respectively), and with the ODI (r = 0.789; P = 0.000 and r = 0.802; P = 0.000, respectively). The adapted Korean version of the RMDQ was successfully translated and showed acceptable measurement properties, and as such, is considered suitable for outcome assessments in the Korean speaking patients with LBP.